PENGARUH STATUS SOSIAL EKONOMI RUMAH TANGGA DAN LINGKUNGAN KELUARGA TERHADAP PERILAKU KONSUMTIF SISWA KELAS VIII SMP NEGERI 1 KARANGREJO TAHUN AJARAN 2017/2018 - Diyah Ayu Nikita; Nafik Umurul Hadi (Universitas Negeri Padang, 2018)
Consumptive behavior regardless of age, gender or social status. Consumptive behavior is dominant among teenagers. Students who are in junior high school begin to enter adolescence and are in the search for identity. In this case they do not have a strong foundation or principle in behavior, especially in consuming. The absence of a strong foundation or principle in behavior can lead to or may lead teenagers to consumptive behavior. This study aims to determine the influence of socioeconomic status of household and family environment partially and simultaneously to consumer behavior of class VIII SMP Negeri 1 Karangrejo academic year 2017/2018. The population in this study is all students of class VIII SMP Negeri 1 Karangrejo academic year 2017/2018. The sampling technique using simple random sampling. Methods of data collection using questionnaires and documentation. The result of the research shows that there is significant influence of socio-economic status of household and family environment to consumer behavior class VIII SMP Negeri 1 Karangrejo academic year 2017/2018 indicated by F count (15,071)> F table (3,11) and significance value 0,000 <0.05. The magnitude of influence of social economic status variable of household and family environment to consumer behavior of class VIII SMP Negeri 1 Karangrejo academic year 2017/2018 that is 26,4% and the rest 73,6% explained by other variable not examined in this research.